2014
DOI: 10.1111/1756-185x.12458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of nonradiographic axial spondyloarthritis in Korea: a comparison with ankylosing spondylitis

Abstract: The predominance of male patients is more prominent among Korean patients with SpA compared with Caucasians. Female nr-axSpA patients had late symptom onset and less progression to AS. X-ray changes at baseline were associated with radiographic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…Symptom onset may precede definite sacroiliitis on plain radiography by years, and recollection of symptom duration can be poor. One retrospective cohort study found the mean time between symptom onset and definite AS by the mNY criteria to be 71 months . Three studies examining individuals with symptom duration less than 2 years found definite sacroiliitis present in 27–38% of subjects .…”
Section: Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…Symptom onset may precede definite sacroiliitis on plain radiography by years, and recollection of symptom duration can be poor. One retrospective cohort study found the mean time between symptom onset and definite AS by the mNY criteria to be 71 months . Three studies examining individuals with symptom duration less than 2 years found definite sacroiliitis present in 27–38% of subjects .…”
Section: Statementmentioning
confidence: 99%
“…These studies examined subjects of various ages, but in each the typical study participant was a male with symptom onset less than 2 years, who had their baseline radiography in their early thirties. Other cohorts of early axial SpA also demonstrate a mean age of onset between 30 and 35 years . One of these studies examined subjects with a mean symptom duration of 4 months and found AS by mNY criteria in 27%.…”
Section: Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Is uveitis as common with nr-Ax-SpA as it is with ankylosing spondylitis? At least two studies indicates that uveitis is as common in non-radiographic disease as it is in ankylosing spondylitis (17, 22). …”
mentioning
confidence: 99%